ANALISIS RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM (KSP) BINA USAHA LAHAT PERIODE 2013-2017 - Armalinda Armalinda (Riset Manajemen dan Akuntansi, 2018)
Savings and Loans Cooperative (KSP) Bina Usaha Lahat Business is one of the business entities engaged in financial cooperatives. This business entity aims to help improve economic growth in the community that cannot be separated from information technology interference every day. Routine activities are carried out every day by carrying out a system of savings and loan transactions with customers. The increasing level of the economy of the community and the increasing capital needs of KSP. Therefore the Lahat Business Development Cooperative is one of the solutions in obtaining and saving funds for the community. This study aims to analyze profitability ratios to measure financial performance. This study uses a type of descriptive quantitative research, through descriptive research that will get an overview of the status of the subject under certain conditions. The method used in data collection is in the form of interviews and direct observation. Ratio of Gross Profit Margin (GPM), Net Profit Margin (NPM) Ratio, Return On Investment Ratio (ROI) and Return On Equity Ratio (ROE) of Savings and Loans Cooperative (KSP) financial performance to Lahat Business GPM ratio with standard measurement> 15% have healthy criteria, at the ratio of NPM with measurement standards> 15% have healthy criteria, on ROI ratio with measurement standards of 7% to